Perinatal Mood and Anxiety Disorder and Reproductive Justice: Examining Unmet Needs for Mental Health and Social Services in a National Cohort - Tanya Khemet Taiwo; Keisha Goode; P. Mimi Niles; Kathrin Stoll; Nisha Malhotra; Saraswathi Vedam (Mary Ann Liebert, 2024)
Introduction: Perinatal Mood and Anxiety Disorders (PMADs) are the most common complications during the perinatal period. There is limited understanding of the gaps between need and provision of comprehensive health services for childbearing people, especially among racialized populations. Methods: The Giving Voice to Mothers Study (GVtM; n=2700), led by a multistakeholder, Steering Council, captured experiences of engaging with perinatal services across the United States, including access, respectful care, and health systems' responsiveness. A patient-designed survey included variables to assess relationships between race, care provider type (midwife or doctor), and needs for psychosocial health services. We calculated summary statistics and tested for significant differences across racialized groups, subsequently reporting odds ratios (ORs) for each group. Results: Among all respondents, 11% (n=274) reported unmet needs for social and mental health services. Indigenous women were three times as likely to have unmet needs for treatment for depression (OR [95% confidence interval, CI]: 3.1 [1.5?6.5]) or mental health counseling (OR [95% CI]: 2.8 [1.5?5.4]), followed by Black women (OR [95% CI]: 1.8 [1.2?2.8] and 2.4 [1.7?3.4]). Odds of postpartum screening for PMAD were significantly lower for Latina women (OR [95% CI]=0.6 [0.4?0.8]). Those with midwife providers were significantly more likely to report screening for anxiety or depression (OR [95% CI]=1.81 [1.45?2.23]) than those with physician providers. Discussion: We found significant unmet need for mental health screening and treatment in the United States. Our results confirm racial disparities in referrals to social services and highlight differences across provider types. We discuss barriers to the integration of assessments and interventions for PMAD into routine perinatal services. Implications: We propose incentivizing reimbursement schema for screening and treatment programs; for community-based organizations that provide mental health and social services; and for culture-centered midwife-led perinatal and birth centers. Addressing these gaps is essential to reproductive justice.